Financial planning as a universal tool in relation to financial performance (GEON Journal (Management, Organizations and Business), 2024)
Problem. The dynamics in which family businessesoperate lead to empirical management. Therefore,the application of financial tools that contribute toimproving their financial performance representsa challenge. Based on the above, it is necessary toachieve the relationship between financial planningand financial performance in order to maintain thesustainability of these business units. Objectives.Explain the relationship between financial planning and financial performance in SMEs in Tierra Blanca, Veracruz. Materials and methods: Methodologically, this work is applied, descriptiverelational, cross-sectional. Two instruments (questionnaires) were applied, the sample is simple random statistics. Results: The results show that there is a positive correlation between financial planning and financial performance. It is shown that companies that have a stability in the market (greater than 7 years of permanence) are favored in the reduction of risks as a result of the proper use of planning, favoring their financial performance. Conclusions: The application of correct financial planning is significantly related to financial performance, with a positive impact. Contribution and originality: Within the literature, there are works that study the variables in companies categorized as large. There are approaches in studies carried out in SMEs, but they do not deepen and establish relationships between variables. Therefore, there are gaps that allow the relevance and originality of this study.
Keywords: Financial planning; SMEs; financial tools; financial performance; financial risks; administration